Temporally controlled overexpression of cardiac-specific PI3Kα induces enhanced myocardial contractility—a new transgenic model - Yano, Naohiro (American Physiological Society, 2008)
The phosphatidylinositol 3-kinase (PI3K) signaling pathway regulates multiple cellular processes including cell survival/apoptosis and growth. In the cardiac context, PI3Kα plays important roles in cardiac growth. We have shown that cardiac PI3K activity is highly regulated during development, with the highest levels found during the fetal-neonatal transition period and the lowest levels in the adult. There is a close relationship between cardiomyocyte proliferation and cardiac PI3K activity. In adult transgenic mice, however, the prolonged constitutive activation of PI3Kα in the heart results in hypertrophy. To develop a strategy to allow temporally controlled overexpression of cardiac PI3Kα, we engineered a tetracycline (tet) transactivator tet-off controlled transgenic mouse line with a conditional overexpression of a cardiac-specific fusion protein of the SH2 domain of p85 and p110α. Cardiac PI3K activity and Akt phosphorylation were significantly increased in adult mice after transgene induction following the removal of doxycycline for 2 wk. The heart weight-to-body weight ratio was not changed, and there were no signs of cardiomyopathy. The overexpression of PI3Kα resulted in increased left ventricular (LV) developed pressure and the maximal and minimal positive values of the first derivative of LV pressure, but not heart rate, as assessed in Langendorff hearts. Mice overexpressing PI3Kα also had increases in the levels of Ca(2+)-regulating proteins, including the L-type Ca(2+) channels, ryanodine receptors, and sarco(endo)plasmic reticulum Ca(2+)-ATPase 2a. Thus the temporally controlled overexpression of cardiac PI3Kα does not induce hypertrophy or cardiomyopathy but results in increased contractility, probably via the increased expression of multiple Ca(2+)-regulating proteins. These distinct phenotypes suggest a fundamental difference between transgenic mice with temporal or prolonged activation of cardiac PI3Kα.